Improved Meet-in-the-Middle Attacks on Reduced-Round Kiasu-BC and Joltik-BC. (3rd July 2019) - Liu, Ya; Shi, Yifan; Gu, Dawu; Zeng, Zhiqiang; Zhao, Fengyu; Li, Wei; Liu, Zhiqiang; Bao, Yang
Abstract: Kiasu-BC and Joltik-BC are internal tweakable block ciphers of authenticated encryption algorithms Kiasu and Joltik submitted to the CAESAR competition. Kiasu-BC is a 128-bit block cipher, of which tweak and key sizes are 64 and 128 bits, respectively. Joltik-BC-128 is a 64-bit lightweight block cipher supporting 128 bits tweakey. Its designers recommended the key and tweak sizes are both 64 bits. In this paper, we propose improved meet-in-the-middle attacks on 8-round Kiasu-BC, 9-round and 10-round Joltik-BC-128 by exploiting properties of their structures and using precomputation tables and the differential enumeration. For Kiasu-BC, we build a 5-round distinguisher to attack 8-round Kiasu-BC with $2^{109}$ plaintext–tweaks, $2^{112.8}$ encrytions and $2^{92.91}$ blocks. Compared with previously best known cryptanalytic results on 8-round Kiasu-BC under chosen plaintext attacks, the data and time complexities are reduced by $2^{7}$ and $2^{3.2}$ times, respectively. For the recommended version of Joltik-BC-128, we construct a 6-round distinguisher to attack 9-round Joltik-BC-128 with $2^{53}$ plaintext–tweaks, $2^{56.6}$ encryptions and $2^{52.91}$ blocks, respectively. Compared with previously best known results, the data and time complexities are reduced by $2^7$ and $2^{5.1}$ times, respectively. In addition, we present a 6.5-round distinguisher to attack 10-round Joltik-BC-128 with $2^{53}$ plaintext–tweaks, $2^{101.4}$ encryptions and $2^{76.91}$ blocks.